Tackling Architectural Complexity with Modeling. - MONTAGNE, KEVIN (Communications of the ACM, 2010)
The article presents a discussion of methods for testing complex computer programs by modeling subsets of their architecture. It is noted that this is a useful method for detecting problems of scaling before extensive resources are committed to systems development, and is also helpful in terms of debugging complicated systems. Examples are provided involving Windows software by Microsoft. The advantages of constructing dummy modules, which can be used to duplicate the performance of a sub-system under various conditions without generating unnecessary data, are described.